National plan for improving seed potato in Georgia - International Potato Center (International Potato Center, 2019)
The objective of the Plan for Improving Seed Potato in Georgia is to provide direction to appropriate Georgian authorities for addressing constraints related to quality seed production in Georgia, especially PSD, in the next five years, 2019-2024. This plan is based on the Integrated Seed Health (ISH) approach which describes three tactics to manage PSD (Thomas-S harma et al. 2015): the adoption of varieties that degenerate slowly due to their natural resistance to the organisms that cause PSD; onfarm practices to maintain or even improve seed quality at the farm level; and strategic use of certified seed (i.e. buying in quantities and at frequencies that correspond to farmers’ needs). Each of these tactics corresponds to a component in the current Seed Plan.